Determination of the optimal electron beam irradiation dose for treating shrimp (Solenocera melantho) by means of physical and chemical properties and bacterial communities. (January 2022) - Yu, Qi; Pan, Huijuan; Qian, Chenru; Shao, Haitao; Han, Jiajun; Li, Yongyong; Lou, Yongjiang
Abstract: Solenocera melantho was irradiated at different doses, and the physiological and biochemical indicators, total viable count, and 16S rRNA were used to study the effect of radiation treatment on the quality of S. melantho . Results showed that irradiating at a dose of 2 kGy killed most microorganisms. The higher the irradiation dose used, the stronger the bactericidal effect observed. The bacterial community structure of the irradiate samples were significantly different from that of the unirradiated samples. Irradiation had no effect on the pH value, although as the irradiation dose increased, polyphenol oxidase activity was effectively inhibited, L* and a* values of the shrimp increased, and springiness of the shrimp muscle was enhanced. Based on these results, an irradiation dose of 6 kGy was found to be the most suitable for the treatment of S. melantho, which provides a theoretical basis for production and processing. Highlights: Electron beam irradiation (EBI) was used to treat Solenocera melantho. The optimal EBI dose for treating Solenocera melantho was determined. 16S rRNA was used to analyze microbial diversity at the end of the preservation. Shewanella and Pseudomonas were killed by EBI.